Addressing Gender and Inclusiveness in Climate, Agriculture, and Resilience Programming - Burke, Robert; Cabriole, Marie Aislinn; Hellin, Jon; Gonsalves, Julian (CGIAR System Organization, 2024)
This policy brief explores key strategies for integrating gender and inclusiveness into resilience programs. Gender-transformative resilience initiatives can challenge gender norms, power dynamics, and social inequalities that increase vulnerabilities in climate-sensitive communities. Ensuring equal access to assets and resources through a gender-transformative approach is vital for building resilience.